Comparison of dietary polyphenols for protection against molecular mechanisms underlying nonalcoholic fatty liver disease in a cell model of steatosis. Issue 9 (20th April 2017) - Rafiei, Hossein; Omidian, Kosar; Bandy, Brian
Abstract : Dietary polyphenols have shown promise in protecting from nonalcoholic fatty liver disease (NAFLD) but little is known of their relative effectiveness and mechanisms. In an in vitro model of NAFLD, exposure of HepG2 hepatocytes to oleic acid increased cellular ROS generation, increased expression of pro‐inflammatory TNF‐α, and decreased mitochondrial biogenesis and content. A comparison of protection by different polyphenols showed similar inhibition of ROS generation, but distinguished those that decreased TNF‐α and increased mitochondrial biogenesis and content. Abstract : Scope: Dietary polyphenols have shown promise in protecting the liver against nonalcoholic fatty liver disease. The relative effectiveness and mechanisms of different polyphenols however is mostly unknown. Methods and results: In a model of steatosis using HepG2 hepatocytes, we evaluated the protective effects of different classes of polyphenols and the contributing mechanisms. The treatment of the cells with oleic acid increased reactive oxygen species (ROS) generation and expression of tumor necrosis factor alpha (TNF‐α), decreased expression of uncoupling protein 2, and decreased mitochondrial content and markers of biogenesis. The treatment with 1–10 μM polyphenols (resveratrol, quercetin, catechin, cyanidin, kuromanin, and berberine), as well as phenolic degradation products (caffeic acid, protocatechuic acid, and 2, 4, 6‐trihydroxybenzaldehyde), all protected by more than 50% against the oleic acid induced increase in ROS. In other mechanisms involved, the polyphenols except anthocyanins strongly prevented or reversed the effect on mitochondrial content/biogenesis, increased expression of manganese superoxide dismutase, and prevented the large increase in TNF‐α expression. Most polyphenols also prevented the decrease in uncoupling protein 2. The anthocyanins were unique in decreasing ROS generation without inducing mitochondrial biogenesis or manganese superoxide dismutase expression. Conclusion: While different polyphenols similarly decreased cellular ROS in this model of steatosis, they differed in their ability to suppress TNF‐α expression and induce mitochondrial biogenesis and content.